Study of the electronic structure of Mn2-хCoxP2O7·5H2O at x=0.6, using X-ray photoelectron spectroscopy - Smolyak Svitlana; Karbivskyy Volodymyr (DataverseUA, 2025)
The electronic structure peculiarities of diphosphate - Mn2-xCoxP2O7·5H2O, at x=0,6, have been studied out by the XPS spectroscopy.